Correlation between ESBL-Producing Bacteria Infection with Sepsis Severity of Patient in Medical Ward of Internal Medicine Department Dr. Soetomo General Hospital in 2016 - Pratiwi, Asri Dhea; Rusli, Musofa; Utomo, Budi (Universitas Airlangga, 2019)
Introduction: Sepsis is life-threatening condition that begins with infections that trigger pro-inflammation overresponse. Delaying antibiotic treatment in sepsis can cause serious condition. In ESBL-producing bacteria, the antibiotic resistance is common and it might cause harm to sepsis patient. This research aims to analyze the correlation between infections of ESBL-producing bacteria with sepsis severity. Methods: This study was observational analytic on sepsis patient in Internal Medicine Ward of Dr. Soetomo General Hospital. The data were taken from medical records of the patient. The severity of sepsis was based on Surviving Sepsis Campaign 2012. Results: A total 72 sepsis patients were included in this study, which consist of 40 patients with non-producing ESBL GNB and 32 patients with ESBL-producing bacteria. The most common bacteria in ESBL infection is Escherichia coli ESBL+ (75%) and non ESBL infection is Acinetobacter baumanii (27.5%). Septic shock is more common in patient with ESBL-producing bacteria (53.1% vs 22.5%). The correlation between ESBL infection and sepsis severity is significant and the power of correlation is low (p = 0.048; r = 0.234). Conclusion: There is a correlation between ESBL-producing bacteria infection with sepsis severity and the power of correlation is low (p = 0.048, r = 0.234).